2022
DOI: 10.1002/jeq2.20358
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mn2+ on Cd accumulation and ionome in rice and spinach

Abstract: Health risks caused by food containing Cd is a concern worldwide. Interaction between Mn and Cd has been widely studied in normal hydroponic solution with high ion activities (e.g., the study on sharing of transporter Natural Resistance-Associated Macrophage Protein 5 between Mn and Cd in rice [Oryza sativa L.]). However, interaction of Mn and Cd in crops like rice and spinach (Spinacia oleracea L.) at field ion activity level is still unknown. Thus, an ethyleneglycoltetraacetate-buffered solution experiment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Numerous studies have confirmed the interaction between heavy metals (such as Cd) and trace metals (Fe, Mn and Zn) in absorption and migration in plants, and these metal transporters including Nramp, CAX (Ca 2+ /H + exchanger antiporter), HMA (heavy metal transporting ATPase), etc. usually do not specifically distinguish between heavy and beneficial metals and transport them separately [1,6,7]. Therefore, accurately identifying important metal transporters and exploring their inherent relationship with metal absorption and migration in plants is crucial for understanding the physiological functions and accumulation patterns of these metal elements in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have confirmed the interaction between heavy metals (such as Cd) and trace metals (Fe, Mn and Zn) in absorption and migration in plants, and these metal transporters including Nramp, CAX (Ca 2+ /H + exchanger antiporter), HMA (heavy metal transporting ATPase), etc. usually do not specifically distinguish between heavy and beneficial metals and transport them separately [1,6,7]. Therefore, accurately identifying important metal transporters and exploring their inherent relationship with metal absorption and migration in plants is crucial for understanding the physiological functions and accumulation patterns of these metal elements in plants.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, more than half of the global population suffers from severe deficiencies in essential trace elements such as Fe and Zn, and plants require multiple essential mineral and beneficial elements to maintain growth and development and resist biotic and abiotic stresses [4,5]. Due to the geochemical behavior similarities of heavy metal elements such as Cd, Pb, and Cr with essential elements like Fe, Zn, and Mn, and the poor specificity of plant metal transport proteins, there exists a certain degree of synergy/antagonism between these heavy-metal and trace-metal elements in their absorption and transfer in plants [6,7]. Therefore, identifying and characterizing important metal transport proteins in plants and their relationships with metal ion content (ionome) are crucial for understanding the molecular mechanisms of metal element absorption and transfer in plants, thereby improving food quality, and preserving human health.…”
Section: Introductionmentioning
confidence: 99%
“…In spinach and in most other crops, the main mechanism of Cd 2+ uptake is mainly via the Zn 2+ uptake pathway (M. Wang et al., 2023 ). One contrasting crop is rice, where the Mn uptake transporter (OsNramp5) is responsible for Cd 2+ uptake (Ishikawa et al., 2012 ; Sasaki et al., 2012 ; M. Wang et al., 2022 ). For a detailed review of the mechanisms of Cd accumulation in higher plants, see (Sterckeman & Thomine, 2020 ).…”
Section: Root Cause Of CD and Pb Accumulation In Spinachmentioning
confidence: 99%
“…On the other hand, the addition of Fe could also reduce Cd content in rice [ 20 ] and enhance rice growth and yield [ 24 ], which suggests that Cd translocation into rice might occur via Fe metabolic pathways [ 25 ]. The interaction between Mn and Cd has also been identified, because the accumulation of Cd is reduced in both roots and shoots in the Mn sufficiency environment compared with the Mn deficiency environment [ 26 ]. Fe and Mn alleviated Cd toxicity by preventing Cd from being absorbed by forming an Fe plaque on the surface of rice roots [ 27 ].…”
Section: Introductionmentioning
confidence: 99%